Odpowiedź :
[tex]1)\\\\a)\\\\(x+3)-(- x+6)= x+3+ x-6=2x-3\\\\b)\\\\6(x-4)- 5+ 2x + 29=6 x-24- 5+ 2x + 29=8x\\\\c)\\\\-5(x-y-1)-4( 2x+2y-3) =-5 x+5y+5-8x-8y+12 =-13x-3y+17\\\\d)\\\\2(3a+4b)-2(a-b)=6a+8b -2 a+2b=4a+10b[/tex]
[tex]e)\\\\ 3a(a-3)+ 3a(-2a+5)-6a=3a^2-9a-6a^2+15a-6a =-3a^2\\\\f)\\\\ (x+3 )(3x-4)=3x^2 -4x+9x-12=3x^2-5x-12\\\\h)\\\\-5a-2ab+ 5ba+2ab-5a +ab-(-ab)=-5a-2ab+ 5ba+2ab-5a +ab+ab=\\\\=7ab-10a[/tex]
[tex]2)\\\\a)\\\\3a+2-a+6+7a= 9a+8\\\\a=2\\\\9a+8=9*2+8=18+8=26\\\\b)\\\\ -2(a+b)+3(a-b)= -2 a-2b+3 a-3b=a-54b\\\\a=0,\ \ \ b=0,2\\\\a-5b=0-5*0,2=0-1=-1[/tex]
[tex]c)\\\\ (3x-2)(x+5)=3x^2+15x-2x-10=3x^2+13x-10 \\\\x=-2\\\\ 3x^2+13x-10=3*(-2)^2+13*(-2)-10=3*4-26-10=12-36=-24\\\\d)\\\\ -0,3k-0,7+3,4k+0,6+0,1=3,1k\\\\k=-1\\\\3,1k=3,1*(-1)=-3,1[/tex]